2022
DOI: 10.1186/s12879-022-07095-x
|View full text |Cite
|
Sign up to set email alerts
|

RT-PCR negative COVID-19

Abstract: Background COVID-19 is a multi-system infection with emerging evidence-based antiviral and anti-inflammatory therapies to improve disease prognosis. However, a subset of patients with COVID-19 signs and symptoms have repeatedly negative RT-PCR tests, leading to treatment hesitancy. We used comparative serology early in the COVID-19 pandemic when background seroprevalence was low to estimate the likelihood of COVID-19 infection among RT-PCR negative patients with clinical signs and/or symptoms c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Before the seventh day of symptom onset, the number of antibodies may be insufficient for the detection and diagnosis of COVID-19 [20] . Therefore, patients presenting with clinical criteria for COVID-19, even those with negative RT–qPCR results, should also receive treatment for acute disease [11] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before the seventh day of symptom onset, the number of antibodies may be insufficient for the detection and diagnosis of COVID-19 [20] . Therefore, patients presenting with clinical criteria for COVID-19, even those with negative RT–qPCR results, should also receive treatment for acute disease [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite limitations such as the long time it takes to release the results, and the possibility of false-negative results due to several factors, the gold standard is the quantitative real-time polymerase chain reaction molecular technique (RT–qPCR) using the reverse transcriptase assay [9] . In addition to the origin of the material collected, the result depends on the time elapsed between sample collection and the onset of symptoms, the fluctuation of viral load, and correct sample collection [9] , [11] , [12] , [13] , [14] , [15] , [16] , [17] . In addition to RT–qPCR, serology, based on the detection of immunoglobulin antibodies in blood, serum, or plasma samples, is also used because it provides rapid results; however, has low sensitivity (15–76 %) and must be performed 7 days after the onset of symptoms [9] , [11] , [17] , [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the dogs’ response would increase the chances for a sample from the Control group being indicated by the dogs as negative to 100%. Assuming that highly sensitive tests are best used for screening, while highly specific tests are best for confirming diagnostics 22 , the high PPV and NPV achieved in the two estimated prevalence scenarios support the potential use of dogs both in sites of high SARS-CoV-2 prevalence to exclude individuals not needing RT-PCR, and in low prevalence sites to complement the standard quick diagnostic test in confirming that the virus is present 42 . Clearly, if a COVID-19 diagnosis is missed, this can lead to delayed, missed, or unneeded treatment for an inaccurate alternative diagnosis.…”
Section: Discussionmentioning
confidence: 77%
“…However, these tests have been noted to have variable sensitivity. One study found that during the first week after symptom onset, false negative rates ranged from 2% to 29% [12].…”
Section: Ct On Initial Encountermentioning
confidence: 99%